A Case of Milk Alkali Syndrome: The Forgotten Diagnosis of Generalized Weakness and Altered Consciousness - Hossain , Md Sabbir; Azad, Md Abul Kalam; Rahaman, Mohammad Ferdous Ur; Aftab, Kazi Ali; Rahman, Imrul Basher; Monira, Shirajum (Bangladesh Journal of Medicine, 2024)
This case reports outlines a 76-year-old male’s progression from papillary thyroid carcinoma diagnosis to the development of Calcium-Alkali Syndrome (CAS) following thyroidectomy. Initially presenting with thyroid mass, surgery was followed by generalized weakness and altered sensorium, investigations that revealed elevated calcium levels ,metabolic alkalosis and renal impairment . Diagnosis pointed to CAS, likely triggered by prescribed calcium and calcitriol post-surgery. Cessation of supplements and hydration resulted in resolution. While postthyroidectomy hypocalcemia is anticipated, CAS poses challenges, especially with increasing calcium supplement use. This emphasizes the need for vigilant monitoring of electrolyte imbalances, particularly in regions with limited follow-up practices. Clinicians should balance preventing hypocalcemia without risking hypercalcemia, stressing the importance of timely identification and tailored interventions to prevent CAS complications. This case underscores the significance of recognizing CAS as a potential postoperative complication, urging vigilant monitoring and tailored management in similar clinical settings. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 174